Association between zidovudine-containing antiretroviral therapy exposure in utero and leukocyte telomere length at birth. (1st November 2019) - Wang, Youjin; Brummel, Sean S.; Beilstein-Wedel, Erin; Dagnall, Casey L.; Hazra, Rohan; Kacanek, Deborah; Chadwick, Ellen G.; Marsit, Carmen J.; Chanock, Stephen J.; Savage, Sharon A.; Poirier, Miriam C.; Machiela, Mitchell J.; et al.
Abstract : Objectives: Zidovudine (ZDV) is a nucleoside reverse transcriptase inhibitor that could cause telomere shortening through inhibition of telomerase. We examined the association between in utero exposure to ZDV and telomere length at birth in HIV-exposed-uninfected (HEU) newborns. Methods: We selected 94 ZDV-exposed HEU children and 85 antiretroviral therapy (ART)-unexposed HEU children from the Surveillance Monitoring for ART Toxicities Study and the Women and Infants Transmission Study. We assessed relative telomere length in stored peripheral blood mononuclear cells taken in the first 7 days of life using quantitative polymerase chain reaction. We used linear regression to compare relative telomere length between ZDV-exposed and ART-unexposed children. We additionally evaluated relative telomere length according to maternal and infant characteristics. Results: Relative telomere length was longer in ZDV-exposed children compared with ART-unexposed individuals (adjusted mean ratio difference 0.21, 95% confidence interval 0.15–0.28, P < 0.001). We found an inverse correlation between maternal HIV RNA levels and infant relative telomere length (−0.06 per log10 copies, 95% confidence interval −0.08 to −0.03, P < 0.001). Relative telomere length was not associated with maternal CD4 + cell count, maternal age, gestational age, sex, sample storage time, or maternal substance use ( P > 0.05). Conclusion: Relative telomere length was longer in ZDV-exposed infants. This difference may reflect beneficial health effects of ART during pregnancy, as we observed an inverse association with maternal HIV RNA levels. Abstract : Supplemental Digital Content is available in the text